2011
DOI: 10.1097/pdm.0b013e31821c30bc
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Molecular Genetic Alterations in GBMs Highlights a Distinctive Molecular Profile in Young Adults

Abstract: To evaluate age-related differences in histopathologic and molecular profile of glioblastomas (GBMs) at various age groups, with special reference to TP53 mutation, epidermal growth factor receptor (EGFR) amplification, EGFR vIII mutant, PTEN deletion, and IDH1 mutation. Agewise GBM incidence was calculated over a period of 5 years (2005 to 2009). Seventy-five GBMs were selected for molecular analysis. Majority of cases were in the age group of 41 to 60 years, and mean age was 43.6 years. Histology of all 75 c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
34
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 40 publications
(38 citation statements)
references
References 0 publications
4
34
0
Order By: Relevance
“…Furthermore, we showed that ALK overexpression is more common in older individuals (>59 years) with IDH1 R132H -negative GBM in keeping with data indicating that the molecular profile of GBM differs between younger and older patients 30. In a recent study assessing ALK expression by immunohistochemistry, no significant difference between young (<45 years) and older (>70 years) patients was reported in 44 IDH1 R132H -negative GBM, but when all GBM (n=48) were evaluated ALK positivity was more prevalent in the younger group 31.…”
Section: Discussionsupporting
confidence: 89%
“…Furthermore, we showed that ALK overexpression is more common in older individuals (>59 years) with IDH1 R132H -negative GBM in keeping with data indicating that the molecular profile of GBM differs between younger and older patients 30. In a recent study assessing ALK expression by immunohistochemistry, no significant difference between young (<45 years) and older (>70 years) patients was reported in 44 IDH1 R132H -negative GBM, but when all GBM (n=48) were evaluated ALK positivity was more prevalent in the younger group 31.…”
Section: Discussionsupporting
confidence: 89%
“…For TP53 mutational analysis, coding regions from exons 2 to 11 were evaluated using the direct sequencing protocol as described in the International Agency for Research on Cancer p53 database and described earlier [14]. Mutations in exon 4 of IDH1 were determined by direct sequencing in all the cases as described in the previous study [15].…”
Section: Methodsmentioning
confidence: 99%
“…Mutations in H3.3 were also highly specifi c for GBMs when compared to low-grade lesions and thus provide additional tools to help differentiate between the different tumor grades in small biopsies [ 11 ]. Although extremely rare in the pediatric population, IDH1 mutations may be encountered in the adolescent age group [ 12 ].…”
Section: Glioblastomamentioning
confidence: 99%